2014
DOI: 10.1007/s00240-014-0682-z
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric urolithiasis: metabolic risk factors and follow-up results in a Turkish region with endemic stone disease

Abstract: The goal of this study was to investigate the metabolic etiology, clinical findings and medical treatment of children with urolithiasis in an endemic region of Turkey. We retrospectively analyzed the medical records of 742 (437 males, 305 females) children with urolithiasis. Physical examination results, serum biochemistry and urine metabolic evaluation, including urinary citrate, oxalate, calcium, uric acid, cystine and magnesium levels were recorded. We obtained follow-up records in 316 patients to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 20 publications
4
13
0
11
Order By: Relevance
“…This percentage was almost similar to other studies conducted in the United States, Mexico, Italy and Turkey [7,14,15,16]. These findings show that regardless of the region and race, most children with urolithiasis have underlying metabolic abnormalities.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This percentage was almost similar to other studies conducted in the United States, Mexico, Italy and Turkey [7,14,15,16]. These findings show that regardless of the region and race, most children with urolithiasis have underlying metabolic abnormalities.…”
Section: Discussionsupporting
confidence: 79%
“…Hypocitraturia was the main metabolic abnormality in older children and adolescents with urolithiasis, which is in accordance with other global studies [9,14,15,22,23,24]. Kovacevic et al [23] indicated that there is a shift from hypercalciuria to hypocitraturia as the predominant metabolic abnormality in pediatric urolithiasis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Medication may be a part of management of children with recurrent nephrolithiasis, solitary kidney, or metabolic disorders. In this context, the result of stone analysis or a 24-hour urine collection analysis plays an important role (33,39,69,70). Thiazides and potassium-sparing diuretics are on top of the list.…”
Section: Prevention Of Recurrencementioning
confidence: 99%
“…Children with metabolic disorders had a higher recurrence rate, so metabolic examination is essential to preventive treatment in children. In the pediatric age group, the most common metabolic disorders are hypercalciuria and hypocitraturia, with hypercalciuria more often found in the endemic areas and hypocitraturia in the nonendemıc areas [3,4]. Metaphylaxis has been found to reduce recurrence rates by about half, even in recurrent kidney stones [5].…”
Section: Introductionmentioning
confidence: 99%